A Robotic Companion for Psychological Well-being: A Long-term Investigation of Companionship and Therapeutic Alliance - Jeong, Sooyeon; Aymerich-Franch, Laura; Alghowinem, Sharifa; Picard, Rosalind W; Breazeal, Cynthia L; Park, Hae Won (Proceedings of the ... ACM SIGCHI. ACM Conference on Human-Robot Interaction, 2023)
Social support plays a crucial role in managing and enhancing one's mental health and well-being. In order to explore the role of a robot's companion-like behavior on its therapeutic interventions, we conducted an eight-week-long deployment study with seventy participants to compare the impact of (1) a with only assistant-like skills, (2) a with additional instructive positive psychology interventions, and (3) a that delivered the same interventions in a peer-like and supportive manner. The companion-like robot was shown to be the most effective in building a positive therapeutic alliance with people, enhancing participants' well-being and readiness for change. Our work offers valuable insights into how companion AI agents could further enhance the efficacy of the mental health interventions by strengthening their therapeutic alliance with people for long-term mental health support.